2016
DOI: 10.1080/07347332.2016.1228095
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, self-blame, and satisfaction with care among patients with lung cancer

Abstract: Despite satisfaction with their treatment and care, lung cancer patients feel that society stigmatizes them as a general population. Patients who smoke are more likely to report that they have personally experienced stigma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 15 publications
3
35
0
1
Order By: Relevance
“…In this study, we, as well as other research groups, have demonstrated that perceived LCS can originate from various sources and take various forms . Perceived stigma from health care professionals can be detrimental, as patients can feel discomfort communicating their symptoms to health professionals, which in turn can lead to delay in presentation, in diagnosis, and in treatment, or even low uptake of treatment .…”
Section: Discussionmentioning
confidence: 82%
“…In this study, we, as well as other research groups, have demonstrated that perceived LCS can originate from various sources and take various forms . Perceived stigma from health care professionals can be detrimental, as patients can feel discomfort communicating their symptoms to health professionals, which in turn can lead to delay in presentation, in diagnosis, and in treatment, or even low uptake of treatment .…”
Section: Discussionmentioning
confidence: 82%
“…quality of life and seeking medical and social support. [19][20][21][22][23][24][25][26][27] Years of antitobacco campaigns and tobacco industry public comments have led many individuals to internalize blame for the connection between smoking and a lung cancer diagnosis. 22,25,28 These messages overlook both mechanistic factors regarding the harmful constituents found in addictive cigarettes and the environmental context that encouraged smoking FIGURE 3 Lung cancer dyads at 5 and 12 months post-diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…b 12-month models controlled for patient stage at diagnosis and sum of treatment modalities on patient self-reported health and caregiver Charlson Comorbidities and education on caregiver self-reported health initiation, often leading to addiction. 19,21,25 At the interpersonal level, many believe those with tobacco-related lung cancer are responsible for their disease, 22,23,25,27,29 and this belief is largely attributable to the decades of "smoker-shaming" messaging. Studies comparing social perceptions of lung to various other cancers have found that because of this perception, most people are less likely to endorse funding for lung cancer research in favor of funding for other cancer research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stigma can threat the identity of the person, and it may be internalized in such a way that results in negative feelings and diminished self-esteem (Goffman, 1963;Corrigan and Watson, 2002). The cancer stigma, particularly, has drawn the attention to the detrimental burden of social views on the lives of some patients with cancer (Carter-Harris and Hall, 2014;Weiss et al, 2017;Bamidele et al, 2019;Dodd et al, 2019). The research so far consistently indicated that in spite of relatively low prevalence, the negative influence of any stigmatization is a part of sufferings imposed by the condition on the patients' lives.…”
Section: Translation and Factor Analysis Of The Stigma Scale For Chromentioning
confidence: 99%